Gluteal muscle activity and patellofemoral pain syndrome: a systematic review. Issue 4 (3rd September 2012) - Barton, Christian J; Lack, Simon; Malliaras, Peter; Morrissey, Dylan
Abstract : Objective: There is growing evidence to support the association of gluteal muscle strength deficits in individuals with patellofemoral pain syndrome (PFPS) and the effectiveness of gluteal strengthening when treating PFPS. In additiona, an impressive body of work evaluating gluteal electromyography (EMG) has recently emerged, further supporting the importance of gluteal muscle function in PFPS. This systematic review synthesises these EMG findings in order to better understand the role of gluteal muscle activity in the aetiology, presentation and management of PFPS. Methods: MEDLINE, EMBASE, CINAHL, Web of Knowledge and Google Scholar databases were searched in September 2011 for prospective and case–control studies evaluating the association of gluteal EMG with PFPS. Two independent reviewers assessed each paper for inclusion and quality. Means and SDs were extracted from each included study to allow effect size calculations and comparison of results. Results: Ten case–control, but no prospective studies were identified. Moderate-to-strong evidence indicates gluteus medius (GMed) activity is delayed and of shorter duration during stair negotiation in PFPS sufferers. In addition, limited evidence indicates GMed activity is delayed and of shorter duration during running, and gluteus maximus (GMax) activity is increased during stair descent. Conclusions: Delayed and shorter duration of GMed EMG may indicate impaired ability to control frontal and transverse plane hip motion. Further research evaluating the value of gluteal muscle activity screening in identifying individuals most likely to develop PFPS, and the effectiveness of interventions targeting changes to gluteal muscle activation patterns is needed.